Does the Global Competitiveness Index Demonstrate the Resilience of Countries to Economic Crises? - Petrylė, Vaiva (Ekonomika, 2017)
The concept of a country’s competitiveness still does not have a clear and straightforward meaning and remains ambiguous. Different economists stress various aspects of the concept and use a number of different methods to evaluate how competitive a country is. This paper focuses on the Global Competitiveness Index, which is calculated by the World Economic Forum and is one of the most well-known measures of competitiveness. The World Economic Forum (2015) defines the competitiveness of a country as a “set of institutions, policies and factors that determine the level of productivity of a country” and argues that productivity “is the main long-run engine for growth, living standards and prosperity”. The definition suggests that a higher competitiveness ranking shows higher productivity of the country’s economy, which should lead to higher and more sustainable economic growth. In addition, economic growth leads to higher living standards and prosperity of the country’s citizens. In the light of the definition, the paper forms the hypothesis that if a country is ranked to be more competitive (i.e., its Global Competitiveness Index is higher), it should have greater resilience to an economic crisis than less competitive countries. In other words, more competitive countries should have higher and more sustainable economic growth rates than the less competitive countries. In order to check this hypothesis, the paper uses the graphical analysis method and examines the relationship between the Global Competitiveness Index and the economic growth of countries during the period of 2006-2015. The research findings show that there is a weak or no relationship between the Global Competitiveness Index and the GDP growth of countries; however, it is a negative relationship between the Global Competitiveness Index and the standard deviation of the country’s GDP growth. The results argue that the Global Competitiveness Index is not capable of forecasting the future GDP growth rates of a country; however, the Global Competitiveness Index indicates if the country avoids sharp fluctuations in its GDP growth rates and maintains sustainable economic growth throughout the period.
Keywords: Competitiveness; country’s competitiveness; Global Competitiveness Index; economic crises